Why are we here? An Investigation of Academic, Employability and Social Facets of Business Undergraduates' Motivation Using Thurstone Scaling - John Buglear (Athens Institute for Education and Research, 2014)
In the UK employability is a key university performance measure. This reflects both the tightening graduate employment market and the demands on the sector for greater accountability. The literature on employability considers the implications for institutions and the student motivation literature examines students' intrinsic and extrinsic goal orientations. This exploratory study complements both areas of work by considering employability, currently deemed an all-pervasive extrinsic goal, as far as students' motivation is concerned relative to the more conventional drivers of decisions to enter higher education; achieving academic success and social fulfilment. It aims to establish both the significance of employability as a motivating factor and ascertain the degree of association with the academic and social factors as well as profile variables. The research design applies Thurstone attitude scaling. Several hundred business undergraduates were asked to encapsulate why they were on their course. The responses were collated and scored by a set of judges against scales of academic, employability and social motivation. The judges' scores were used to determine the most appropriate statements to use in the research instrument, which was then used to survey the attitudes of 75 students. The results suggest that employability is a significant aspect of students' motivation and is associated with the academic and social aspects of motivation. This significance of employability suggests effective learning support strategies are likely to be those that are based on experiential and skill-driven learning alongside more tightly drawn cognitive approaches. The balance of motivational aspects can also inform institutions' student recruitment.